You need to bring the terms to a common denominator, such that:
`8 + 18/w = 14 => 8w + 18 = 14w`
You need to isolate the terms that contain w to one side, such that:
`18 = 14w - 8w => 18 = 6w => w = 18/6 => w = 3`
Since `w!=0` , hence `w = 3` is a valid value.
Hence, evaluating `w` , under the given conditions, yields `w = 3` .
The equation 8+18/w=14 has to be solved for the variable which here refers to w.
Add -8 to both the sides
8+18/w - 8 = 14 - 8
18/w = 6
Divide both the sides by 6
(18/w)/6 = 6/6
3/w = 1
Multiply both the sides by w
(3/w)*w = 1*w
3 = w
The solution of the equation is w = 3
We'll start wtih the original equation:
We'll subtract 8 from both sides:
18/w = 14 - 8
We'll combine like terms from the right side:
18/w = 6
We'll cross multiply:
18 = 6w
We'll divide by 6 both sides and we'll use symmetric property:
w = 3
The value of the variable w that verifies the given equation is w = 3.